Churches in Ecumenical Transition: Toward Multicultural Ministry and Mission (International review of mission, 2012)
This is a brief introduction to the contribution of the Ecumencial Network for Multicultural Ministry (ENFORMM) to the new WCC affirmation on mission and evangelism, which was specifically commissioned by CWME in 2009 and will be fed into the new WCC affirmation on mission evangelism. Recognizing the critical significance of the emerging multicultural and migrant churches to mission and ministry in the twenty-first century, CWME is keen that the new mission statement adequately reflects that important development. Clearly, the ministry and ecclesiology of migrant/multicultural churches are integral to the future mission and existence of the Christian church. “Cultural diversity as a fact of human existence”: This text assumes that cultural diversity is a fact of human societies, and migration is a fact of human existence. Throughout human history, societies have always enjoyed varied degrees of cultural pluralism largely because migration is a natural human predisposition. Migration is by no means limited to movements from South to North. People movements from South to South and North to South have equal importance and impact. With increased migration come increased cross-cultural encounters and their attendant complexities. The paper highlights the unfortunate but pervasive and widespread misconception that migrants as such constitute the root cause of social tension and problems. The paper argues that “people movement around the globe (migration) not only calls for reframing the rhetoric on migration, it also calls for reframing the debate on mission.” “Cultural diversity as a fact of Christian communal life – migration-shaped early church”: The paper asserts that “the Early Church was not homogeneous. Inclusive multicultural practices have been a distinctive characteristic of Christ's church from its very inception.” Similarly, the paper examines the issue of a migration-shaped church and the unam sanctam, exploring how this concept relates to our new reality in mission. It also says under the heading of Multicultural ministry and the ecumenical enterprise that “we are made aware of the need to develop relevant mission and ministry in the context of local multicultural partnerships, taking into account the experiences of locally emerging multicultural churches.” There is a considerable examination of the area of WCC mission statements and emerging migrant/multicultural churches. Key ideas dating back to Tambaram are explored as is the programme on Ecumenical sharing of resources, which is revisited and of which it is said “Churches largely failed to implement the principle of ecumenical sharing and reciprocity in relationships with newly emerged (migrant and multicultural) churches in their own contexts.” The changed map of Christianity in Western countries was not taken seriously for a long time. This meant that the “old” churches continued to dominate the Christian scene, sometimes based on the premise that migrant churches presented a fragmented and fluid scene. Although there is some truth to this, it is important to recognize that migrant and multicultural churches do not constitute a temporary expression of church, and that their existence is a natural part of societies that have changed. “Responses to migration”: The paper notes a tendency to problematize the “migrant-foreigner” as the cause of all social ills which plays a key role in the now recurring popular opposition to multiculturalism. The notion of multiculturalism that we subscribe to and which informs and shapes our multicultural practices entails deep and meaningful inter-social engagement, mutual understanding and respect. It demands systemic racial justice. This understanding of multiculturalism is implicit throughout this paper (particularly in 3.4, paragraphs 1–4), though for obvious reasons the language of multicultural church and ministry is used. “Winds of change: migration as a new missional framework”: The scene is now set for a new phase in the history of mission, as Christians of all nations can join locally in multicultural mission and ministry to the community and communities. For effective witness and service we urgently need a Christian hermeneutic of migration that adequately equips and enables faith communities to grasp the complexities (both gifts and challenges) of cultural diversity from the perspective that all people are God's and that healing of the nations constitutes both eschatological promise and hopeful mission in the present. It is in the laboratory of local migrant and multicultural congregations that new ways of rendering missional service to the community are developed. Diversity here is seen as a gift of God, evident in the use of the plural “churches” in the New Testament and in a variety of eschatological themes and insights in individual apostolic letters. Still missing is an understanding of cultural diversity as absolutely integral to the oneness of the body of Christ – a missing element that ENFORMM in this paper wishes urgently to be addressed. “Winds of change” conclusions: The church is a “pilgrim church” in nature and in its missionary enterprise “in pilgrimage”. The church of Christ therefore is a church of migrants, who live by Peter's word that we are “sojourners and pilgrims”. Emerging multicultural churches, both in ministry and mission, push for a new understanding of Christian life: they embrace diversity in unity; they seek to establish Christian identity while in pilgrimage; they seek recognition as equal partners in ecumenical relations and missional work. Migration and multicultural ministry are core issues for mission, evangelism and ecclesiology for the twenty-first-century church. This new framework requires a new understanding of mission and ministry that emphasizes the crossing of boundaries, openness to cultural encounters, courage to face inevitable complexities, appreciation of different values as sources of strength, and intentional efforts at cross-cultural dialogue to build new relationships. The church, living in a multi-ethnic world, has always been a culturally diverse body, shaped by migration. The WCC's Churches Commission on International Affairs (CCIA) has recently highlighted migration as one of its focal areas. The boundaries of Christian community need to be redefined and transcended with respect to nationhood, language, ethnicity and status. Successive WCC assemblies and mission conferences in the latter parts of the twentieth century have addressed the issues of migration and cultural diversity briefly. Now it is time to give these critical issues the necessary focus, given the unprecedented levels of global migration and its very public and visible implications for the world church and societies. ENFORMM makes several strong recommendations in the paper that draw attention to the critical importance of multicultural ministry for mission in the twenty-first century and beyond and urges WCC to give serious commitment to meaningful engagement with the issue. Giving serious and sensitive attention to migration and multicultural ministry in the new WCC mission statement is an invaluable way to signal the priority and urgency they warrant for Christian mission thinking and practice now and into the future. Katalina TAHAAFE-WILLIAMS